TEKNOLOGI INFORMASI KOMUNIKASI DAN PERTUMBUHAN EKONOMI WILAYAH BARAT DAN TIMUR INDONESIA PERIODE 2014-2018 - Wardhana, Adhitya; Kharisma, Bayu; Lisdiyanti, Tresna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.11.TAHUN 2020DO - 10.24843/EEB.2020.v09.i11.p05, 2020)
The purpose of this research will be to try to analyze the influence of information and communication technology ( TIK ) on economic growth in western and eastern Indonesia. This research is a descriptive and quantitative analysis of provinces in Indonesia with the scope divided into western and eastern Indonesia. For western Indonesia as many as 16 provinces, while eastern Indonesia is 17 provinces. The source of the research data was obtained from the Central Bureau of Statistics. The research model used is the  Generalized Least Square model. The results showed that information and communication technology ( TIK ) in eastern and western Indonesia has an effect on economic growth, but its utilization is more widely done by Western Indonesians than the eastern regions of Indonesia.